The Death and Rebirth of the Feminine Muse: Edgar Allan Poe and Sylvia Plath - Ibrahim, Noha (AUC Knowledge Fountain, 2023)
While drawing on mythology and a literary history that associated women with death as well as creativity, Edgar Allan Poe and Sylvia Plath experimented with binary oppositions such as masculine/feminine, composition/decomposition, and death/(re)birth. They gained inspiration from the same source, the dead muse, but how do they transform traditions that derive from classical and medieval literary precedent, perhaps in ways that are inherently critical of patriarchal modes of gender dynamics? Why is Poe fixated on a feminine dead muse while Plath is inspired by what she calls her “father-sea-god muse”? How do both authors represent the female body, and how do they link it to death and rebirth? This thesis centralizes the dead muse as a literary and cultural symbol through close readings of Poe and Plath that examine selected poems and key prose statements that enable their creative work to be viewed in sociosexual terms as an adventure of writing, the imagination and the human body.